Fallen angels - Myers, Walter Dean, 1937- (New York, NY : Scholastic Inc., 2008)
Seventeen-year-old Richie Perry, just out of his Harlem high school, enlists in the Army in the summer of 1967 and spends a devastating year on active duty in Vietnam
Includes excerpt from Sunrise over Fallujah and an interview with the author
Coretta Scott King Award, author, 1989
Keywords: African Americans -- Juvenile fiction; War stories; Vietnam War, 1961-1975 -- Juvenile fiction; Vietnam War, 1961-1975 -- Fiction; African Americans -- Fiction; War -- Fiction